A comparison of transit-time flowmetry and intraoperative fluorescence imaging for assessing coronary artery bypass graft patency. - Balacumaraswami, L; Abu-Omar, Y; Choudhary, B; Pigott, D; Taggart, D (2005)
BACKGROUND: Intraoperative graft patency assessment during coronary artery bypass grafting enables detection and immediate correction of graft failure. Currently transit-time flowmetry is used to assess graft patency on the basis of mean graft flow and derived values, such as the pulsatility index. Intraoperative fluorescence imaging, based on the fluorescence of indocyanine green dye, provides direct visual images to confirm graft patency. METHODS: We performed a prospective observational study to assess intraoperative graft patency in patients undergoing coronary artery bypass grafting, by using an intraoperative fluorescence imaging system (SPY) and transit-time flowmetry (BF 2004). Poor flow with the intraoperative fluorescence imaging system was defined if there was an absence of fluorescence or if it did not appear within 15 seconds in the graft. A persistent mean graft flow value less than 5 mL/min and a pulsatility index greater than 5 with transit-time flowmetry were considered unacceptable and prompted graft revision. RESULTS: We assessed the intraoperative patency of 266 grafts in 100 coronary artery bypass grafting patients. Intraoperative fluorescence imaging and transit-time flowmetry confirmed adequate flow in 241 (91%) grafts in 75 patients (75%). Transient poor flow was detected with both intraoperative fluorescence imaging and transit-time flowmetry in 7 (2.6%) grafts in 7 (7%) patients. This subsequently proved to be adequate on repeat testing and hence did not necessitate graft revision. Both intraoperative fluorescence imaging and transit-time flowmetry confirmed persistent poor flow in 8 (3%) grafts in 8 (8%) patients that necessitated graft revision. However, in a further 10 (3.8%) grafts in 10 (10%) patients, transit-time flowmetry indicated persistently poor flows on the basis of mean graft flow and pulsatility index values, whereas the intraoperative fluorescence imaging system demonstrated satisfactory flow. These grafts were not revised. CONCLUSIONS: In most patients, both intraoperative fluorescence imaging and transit-time flowmetry are useful to confirm intraoperative graft patency. However, in a small proportion of patients (10%), graft patency assessment with transit-time flowmetry alone might prompt unnecessary graft revision.